Clinical outcomes of surgical treatment and longitudinal non-surgical observation of patients with subclinical Cushing′s syndrome and nonfunctioning adrenocortical adenoma - Takeshi Maehana; Toshiaki Tanaka; Naoki Itoh; Naoya Masumori; Taiji Tsukamoto (Indian Journal of Urology, 2012)
Aims: To investigate the outcomes of the surgical management and longitudinal assessment of patients with subclinical Cushing′s syndrome (SCS) and nonfunctioning adrenocortical adenoma (NFA). Materials and Methods: Between the years 1995 and 2008, 73 patients with asymptomatic adrenocortical adenoma were enrolled. They were informed of the risks and benefits of adrenalectomy and conservative management, and then chose the treatment. Results: SCS was observed in 13 patients (17.8%) and NFA in 60 patients (82.2%). Tumor size in SCS was significantly larger than that in NFA (34.6 ± 9.7 mm vs. 24.5 ± 8.0 mm in diameter, P=0.001). Of the SCS patients, 7 also suffered from hypertension (HT), 2 from diabetes mellitus (DM) and 3 from hyperlipidemia (HL). After adrenalectomy, the insulin dose could be reduced in 2 (100%) patients with DM, in 5 (71.4%) of those with HT and in 2 (66.7%) of those with HL. In the NFA surveillance group, 1 (2.6%) case developed into SCS 3 years after the initial presentation and an increase in size of the tumor was observed in 1 (2.6%), with a mean follow-up of 51.2 months. Conclusions: Surgical resection may be beneficial for the control of SCS and is likely to provide improvement of concomitant HT, DM and HL. Although NFA can be managed conservatively, its size and hormonal activities may change longitudinally. Thus, long-term follow-up is necessary for NFA.